2022
DOI: 10.3390/v14071404
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Deubiquitinating Enzymes Interfere with the SARS-CoV-2 Papain-like Protease and Block Virus Replication In Vitro

Abstract: The ubiquitin proteasome system (UPS), particularly its deubiquitinating enzymes (DUBs), play a key role in the replication cycle of coronaviruses. The SARS-CoV-2 papain-like protease (Plpro) is known to process the viral polyproteins to form the replicase transcriptase complex and to counteract the host viral response. Recently, it was shown that this viral protease can also act as a deubiquitinating enzyme. In this study, we demonstrate that certain DUB-Inhibitors (DIs) interfere with SARS-CoV-2 replication.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…More recently, Setz et al (2017) reported a 90% reduction in the replicative capacity of the human immunodeficiency virus (HIV-1) in lymphoid cells after treatment with PR-619 [ 33 ]. Interestingly, Große et al (2022) found that DUB inhibitors interfere with SARS-CoV2 Papain-like protease enzymatic activity in a dose-dependent manner, thus impairing viral replication [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Setz et al (2017) reported a 90% reduction in the replicative capacity of the human immunodeficiency virus (HIV-1) in lymphoid cells after treatment with PR-619 [ 33 ]. Interestingly, Große et al (2022) found that DUB inhibitors interfere with SARS-CoV2 Papain-like protease enzymatic activity in a dose-dependent manner, thus impairing viral replication [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a proteomics study has identified over 98 ubiquitin ligases and 29 deubiquitinating enzymes that interact with SARS-CoV-2 proteins [ 52 ], underlining the relevance of this post-translational modification not just for the host but also viral proteins. Understanding this interface might lead to the development of novel therapeutic approaches, such as targeting deubiquitinating enzymes to suppress SARS-CoV-2 replication [ 53 ]. These combined findings underline the need for further research to comprehend the intricate network of the ubiquitination and deubiquitination processes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to manipulating host's ubiquitin regulation system, SARS-CoV-2 can also encode PLpro enzyme, which possesses deubiquitinating and deISGylating activity (Freitas et al, 2020;Klemm et al, 2020;Freitas et al, 2022). Researchers have pointed out that PLpro's capacity to disengage ISG15 from ISGylated modifications may prove to be critical to the virus's replicative cycle (Swaim et al, 2021;Große et al, 2022). Moreover, PLpro's de-ISGylation activity impinges significantly on immune responses.…”
Section: Dub and De-isgylating Activity Of Plpromentioning
confidence: 99%